Atomic force microscopy - Eaton, Peter; West, Paul. (Oxford : Oxford University Press, 2010)
Atomic force microscopes are very important tools for the advancement of science and technology. This book provides an introduction to the microscopes so that scientists and engineers can learn both how to use them, and what they can do.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Atomic force microscopy